2024
DOI: 10.1126/sciadv.adj4289
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of hot drought across western North America since the 16th century

Karen E. King,
Edward R. Cook,
Kevin J. Anchukaitis
et al.

Abstract: Across western North America (WNA), 20th-21st century anthropogenic warming has increased the prevalence and severity of concurrent drought and heat events, also termed hot droughts. However, the lack of independent spatial reconstructions of both soil moisture and temperature limits the potential to identify these events in the past and to place them in a long-term context. We develop the Western North American Temperature Atlas (WNATA), a data-independent 0.5° gridded reconstruction of summer maximum tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…Exceptional warming in western North America has been linked to a combinat natural variability and anthropogenic forcing [1,18,28,[53][54][55], and many of these fa likely contributed to the temperature variability (Figure 3) at MSJSP, but at differen poral scales. For natural forcing, we found that during 1960-2020, late spring (April-PDO conditions were positively associated with instrumental Tmin (r = 0.54, p < Instrumental Tmin also is positively associated (r = 0.43, p < 0.05) with ENSO cond during April-July.…”
Section: Mechanisms Of 21st Century Warmingmentioning
confidence: 99%
See 4 more Smart Citations
“…Exceptional warming in western North America has been linked to a combinat natural variability and anthropogenic forcing [1,18,28,[53][54][55], and many of these fa likely contributed to the temperature variability (Figure 3) at MSJSP, but at differen poral scales. For natural forcing, we found that during 1960-2020, late spring (April-PDO conditions were positively associated with instrumental Tmin (r = 0.54, p < Instrumental Tmin also is positively associated (r = 0.43, p < 0.05) with ENSO cond during April-July.…”
Section: Mechanisms Of 21st Century Warmingmentioning
confidence: 99%
“…Summertime (June-August) temperatures in the southwestern US during the first two decades of the 21st century have been unmatched since at least the mid-1500s and are likely a consequence of anthropogenic warming [1]. The human and environmental consequences of increasing temperatures in this region are broad and ongoing and include changes to fire activity, snowpack and water resources, growing season length, and drought frequency.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations